The Effect of Meditation on Stress Reduction among College Students: A Quantitative Study - Batubara, Juliana; Sinta, Roma; Panjaitan, Firta (PELNUS | Pen en Light for Natural Union of Science, 2025)
This study examines the effect of meditation on stress reduction among college students. The increasing prevalence of stress-related issues in academic environments has raised concerns about the mental health and well-being of students. Meditation, particularly mindfulness practices, has been widely studied for its potential to alleviate stress and enhance emotional resilience. This research aims to assess whether regular meditation can reduce perceived stress levels and improve overall well-being in college students. A total of 60 college students participated in an 8-week meditation program, with pre- and post-intervention stress levels measured using the Perceived Stress Scale (PSS). The results indicated a significant reduction in stress levels following the meditation intervention, with participants reporting improved emotional regulation, focus, and academic performance. These findings suggest that meditation can serve as an effective and accessible tool for managing stress among college students. The study highlights the importance of incorporating mindfulness practices into student wellness programs, offering a low-cost, sustainable approach to promoting mental health in academic settings. Further research is recommended to explore the long-term effects of meditation and its applicability across diverse student populations.